A 2020 Update on Public Awareness of Head and Neck Cancers. (February 2022) - Torabi, Sina J.; Kasle, David A.; Su-Velez, Brooke M.; Mehra, Saral; Day, Terry A.; Yarbrough, Wendell G.; St. John, Maie; Judson, Benjamin L.
Objective: To assess knowledge regarding head and neck cancers (HNCs) in 2020, factors associated with knowledge of the role of human papillomavirus (HPV) in HNCs, and factors associated with exposure to Oral, Head and Neck Cancer Awareness Week (OHANCAW). Study Design: Cross-sectional survey. Setting: Online. Methods: The survey was distributed to 517 participants via a paid panel and utilized US Census–built quotas to represent the US population. Results: Participants surpassed 50% awareness rates in only 5 of 10 (50.0%), 2 of 6 (33.3%), and 5 of 9 (55.5%) preselected answer choices for subsites, risk factors, and signs/symptoms of HNCs, respectively. Knowledge of HPV's role in oropharyngeal cancer was also low, at 30.6%. However, of the controlled variables, exposure to OHANCAW was closely associated with knowledge of HPV's role in HNC (odds ratio, 10.25; 95% CI, 5.36-19.62). Women and elderly individuals were less likely to be exposed to OHANCAW, while those with higher education, those who drink heavily (>4 drinks/d), and current but not former tobacco users were more likely to be exposed. Conclusions: Knowledge of HNCs and the causal role of HPV remains suboptimal, though our results suggest that OHANCAW remains a viable educational pathway. However, certain at-risk populations, such as former smokers and older individuals, whom we may not be effectively reaching and screening, represent a priority for future outreach efforts.